Food security and sustainability: exploring Japanese youth participation in agriculture - Saili, Abdul Rahman; Saili, Jamayah; Aziz, A.S.A; Kamil, M.Z; Aziz, N.N.H (Rynnye Lyan Resources, 2020)
There are many challenges in assuring the sustainability of food supply in the context of expanding Japanese population. Insufficient participation of Japanese youth in the agricultural industry is among the issues in food sustainability which has prompted the Japanese government to ensure more youth engagement in the sector for its continuity. The youth are considered as vanguards who would bring changes in the Japanese agriculture industry as the number of ageing farmers in the country is increasing. In Japan, agriculture is one of the most important industries as it contributes about 1.1% to overall national GDP. Thus, a qualitative study with a phenomenological approach was conducted with 7 Japanese youth who are involved in the agriculture industry in the country to identify their socio-economic characteristics, to determine the factors influencing their participation and the constraints, and to assess the perceptions, perspectives, and understandings of youth towards food security, safety and sustainability in agriculture development. The in-depth face-to-face interviews were used to collect data from 7 young Japanese farmers using both purposive and snowball sampling based on the availability of youth farmers in Japan. The data were analysed and categorized into 5 broad themes. The analysis revealed that family support, tradition, passion, economic factor, and working environment are the factors that influence their participation in the industry. It can be suggested that participation of youth in Japan agriculture industry can be nurtured and sustained with several promotional approaches to youth on what the industry can offer them and their country in the future. Moreover, the motivational drive from their families would undoubtedly encourage them to join the industry. These findings are expected to have significant information and knowledge to extend the literature on Japanese youth participation in agriculture and help formulate the action plan needed for the youth development strategies for Japan agriculture in the future.